Does time exist in quantum gravity? - Kiefer, Claus (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2015)
Time is absolute in standard quantum theory and dynamical in general relativity. The combination of both theories into a theory of quantum gravity leads therefore to a “problem of time”. In my essay, I investigate those consequences for the concept of time that may be drawn without a detailed knowledge of quantum gravity. The only assumptions are the experimentally supported universality of the linear structure of quantum theory and the recovery of general relativity in the classical limit. Among the consequences are the fundamental timelessness of quantum gravity, the approximate nature of a semiclassical time, and the correlation of entropy with the size of the Universe.
Keywords: cosmology; arrow of time; entropy; quantum gravity